Semiotic Analysis of Depression Representation in the Short Film "The Sign" on Nicky K .'s Youtube Channel (International Journal of Cultural and Social Science, 2022)
As many cases of suicide are caused by depression, researchers are interested in researching what causes depression in a person. This study aims to determine how depression is represented in the short film “The Sign” by Nicky K through John Fiske's semiotic analysis. This film depicts how a child goes through his bad days without anyone caring about the inner pressure he receives. This research uses descriptive qualitative research. The author chose this study because of the lack of public attention related to depression cases around him. The author wants to know how depression is portrayed in this film, through behavior, traits that make it a depressive disorder. Researchers want readers to be more sensitive to cases like this. Therefore, the writer is interested in the title of this research. The results of this study indicate that there is a representation of depression in this short film which is seen from the three levels proposed by John Fiske. There are three levels, namely the level of reality, the level of representation and the level of ideology